PERTUKARAN SOSIAL ANTARA TAUKE DAN PETANI KELAPA DI DESA SAKA PALAS JAYA KECAMATAN PELANGIRAN KABUPATEN INDRAGIRI HILIR - Angga Saputra; Indrawati " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2021)
This research was conducted in Saka Palas Jaya Village, Pelangiran District, Indragiri Hilir Regency. The problem studied is about how the socio-economic relationship is formed between the Tauke and Coconut Farmers. After that, an analysis of the Social Exchange contained therein is carried out based on certain propositions. In selecting research subjects, it is done by setting certain criteria (purposive sampling). For the data collection process, the author uses interview guidelines and conducts in-depth interviews with all research subjects with the aim of obtaining valid data. The results in this study explain that there is a socio-economic relationship between the Tauke and Coconut Farmers. The social relations that are formed have made the Tauke and Coconut Farmers to maintain a cooperative relationship between buying and selling coconut. Cost and Reward affect the socio-economic relationship. The lower cost and the bigger rewards they get makes them feel comfortable while subscribing to each other. After knowing the socio-economic relationship in practice, an analysis of socio-economic relations is carried out using a series of propositions contained in the theory used, namely the Social Exchange Theory. After the analysis was carried out, it was found that all the propositions contained in the Social Exchange Theory are in the socio-economic relationship between Tauke and Coconut Farmers. The propositions referred to are the Proposition of Success, Stimulus, Value, Deprivation-Saturation, Aggression-Agreement and Rationality. Keyword: Tauke, Coconut Farmers, Socioeconomic, Social Exchange